2019
DOI: 10.1049/el.2019.1439
|View full text |Cite
|
Sign up to set email alerts
|

Up to 80 Gbaud DP‐16QAM operation using InP‐based high‐bandwidth coherent driver modulator

Abstract: The authors obtained very good back‐to‐back bit error rate performance in up to 80 Gbaud DP‐16QAM operation by using their coherent driver modulator of a 3‐dB electro‐optic bandwidth of over 50 GHz. To achieve high bandwidth and good signal integrity, they used double ultra‐low loop wires between the driver IC and the modulator and a differential capacitively loaded travelling‐wave RF electrode based on straight coupled coplanar waveguide with a ground‐signal–signal‐ground configuration for their InP modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These results confirmed that the bandwidth of the HB-CDM with the CMOS driver is high enough for 64-Gbaud or faster baud rates of up to 80 Gbaud, which correspond to a net data rate of 500-Gb/s capacity per wavelength. Furthermore, the BER characteristics of our HB-CDM with the CMOS driver are equivalent to those of the HB-CDM with the SiGe driver [20]. We have succeeded in significantly reducing power consumption without degrading the high-speed operation characteristics.…”
Section: Small-signal Eo Responsementioning
confidence: 92%
“…These results confirmed that the bandwidth of the HB-CDM with the CMOS driver is high enough for 64-Gbaud or faster baud rates of up to 80 Gbaud, which correspond to a net data rate of 500-Gb/s capacity per wavelength. Furthermore, the BER characteristics of our HB-CDM with the CMOS driver are equivalent to those of the HB-CDM with the SiGe driver [20]. We have succeeded in significantly reducing power consumption without degrading the high-speed operation characteristics.…”
Section: Small-signal Eo Responsementioning
confidence: 92%
“…1, these transmission distances of 1122 and 336.6 km are, to the best of our knowledge, the longest in field experiments using DSP-ASIC-integrated real-time optical transponders with net data-rate > 0.4 Tb/s/carrier. The signals are generated and detected with our newly developed transponder that integrates a DSP-ASIC based on 16-nm complementary metal-oxide-semiconductor (CMOS) technology [17] and a high-bandwidth coherent driver modulator (HB-CDM) based on indium phosphide (InP) technology [18]. The modulation order must be higher than 16 to realize a capacity of >0.4 Tb/s/carrier with the symbol rate of ∼64 GBaud.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental equipment was placed at building A; building B was only for directly connecting transmission lines. Our newly developed optical transponder consists of the DSP-ASIC based on 16nm CMOS technology [17], an InP-based HB-CDM [18], high-bandwidth intradyne coherent receiver (HB-ICR), and micro-integrable tunable laser assemblies (µITLAs) for signal and local oscillator (LO) sources. The measured signal was generated in the optical transponder; the electrical signals output from the DSP-ASIC were modulated by the InP-based HB-CDM in the optical frontend (FE) with the optical carrier output from a µITLA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a high-bandwidth coherent driver modulator (HB-CDM) [1][2][3] and a high-bandwidth intradyne coherent receiver [4,5] have achieved high-speed operation up to 64 GBd with higherorder modulation formats up to 64QAM, and they are key components for constructing large-capacity optical communications systems. These modules employ surface mount lead structures for the RF interface.…”
mentioning
confidence: 99%